Analysis and control of resonant cavity flows - Roberts, David (Cranfield University, 2013)
Recently, the trend for the internalisation of stores within an aircraft fuselage has led to a renewed interest in the field of cavity aero-acoustics. Many modern military aircraft, including recent unmanned combat configurations, are designed with internal stores carriage. Housing stores within a weapon bay cavity has the two fold benefit to the aircraft: reduced excrescence drag, and a smaller radar signature. However, open cavities exposed to a grazing flow can exhibit large resonant pressure fluctuations which may damage stores or components within the cavity. The aim of this research is to investigate the fundamental flow characteristics of open cavities and to develop passive palliative concepts to control the unsteady pressure fluctuations within resonant cavity flows. The fundamental flow characteristics of two scale cavities were investigated experimentally: a 1/40th scale model under transonic conditions (0.80<M∞<0.95) and a 1/20th scale configuration under both transonic (M∞=0.70) and supersonic (M∞=1.5) freestream conditions. Cross-correlation and auto-correlation analyses were used to identify the fundamental time signatures, which are related to the generation of the unsteady pressures within the cavity. The key features within the spectra were identified through Fourier analyses and this assisted in the development of a passive control concept based on resonant absorbers. The temporal characteristics identified from the correlation analyses were linked to a previously proposed generation mechanism for the unsteady pressure modes within the cavity flow. This mechanism links the characteristic travel time of the vortices shed from the cavity front wall, the pressure waves within the cavity, and the frequency of the high intensity modal peaks recorded within the unsteady pressure spectrum. The current work provides the first experimental evidence to support this proposed modal generation mechanism under transonic conditions (0.85<M<0.95). The modal attenuation from a series of passive acoustic absorbers, primarily based on arrays of Helmholtz type resonators, has been investigated and analytical design rules have been developed based on both the wind tunnel test results and separate impedance tube investigations. Within the cavity flow, resonant arrays have demonstrated significant peak attenuation levels with up to 15dB for transonic (M=0.95) conditions and up to 26dB for supersonic (M=1.5) conditions. These new results demonstrate the potential of resonant arrays as passive palliative devices. The attenuation under supersonic conditions is of particular interest, as resonant arrays could support the more widely used spoiler palliatives under the supersonic conditions where spoilers can be less effective. A preliminary investigation into the feasibility of resonant arrays for a full-scale application has also demonstrated the potential of the devices for full-scale use.